PENYULUHAN HUKUM MENGENAI HUKUMAN MATI DI KABUPATEN HALMAHERA TIMUR, PROPINSI MALUKU UTARA - Nardiman, Nardiman (Universitas Esa Unggul, 2021)
East Halmahera Regency, which is located in North Maluku Province, is a splintering area from Maluku Province in 1999. East Halmahera Regency is inhabited by the Tagutil tribe. People in East Halmahera, some of the people live from farming and hunting in the forest. In March 2019, the defendant Habel Lilinger alias Hambiki or Niklas Dilingar and his friends (as many as 6 people) were tortured and murdered against the victims, namely Harun Muharam, Halim Difa, Yusuf Halim, Karim Abdul Rahman and Habibu Salatun, which resulted in Yusuf Halim, Karim Abdul Rahman and Habibu Salaton died, while Halim Difa and Must Muharam suffered wounds. Persecution and murder were carried out in very, cruel, sadistic, cruel and inhuman ways, namely by repeatedly throwing river stones, shooting at the victim, stabbing with a spear, cutting or slashing the victim using a machete on the victim's hand, body and face repeatedly. , so that the victim's face is crushed and difficult to recognize, even though the victim is already in a helpless state. There is a need for legal counseling to citizens in East Halmahera, so as not to do eigenrichting which results in the death of victims and injuries, especially as our country as a rule of law, all problems in society must be resolved according to law. If the victims and the defendants did not know each other, it was only because of a moment's emotion which had fatal consequences. Between the victims and the defendants were still residents of East Halmahera district, only different villages, the defendants were from Dodaga village, while the victims were from Waci village. Keywords : Legal counseling, death penalty, East Halmahera Regency